Factor analysis satisfaction levels of users toward the JKN mobile application in the COVID-19 Era using the PIECES framework - Gustiawan, Randa; Pribadi, Ulung (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2022)
This study aimed to prove the researcher's hypothesis regarding users’ factor analysis satisfaction of the Mobile JKN application in the Covid-19 era in Sungai Penuh City using the PIECES framework. The measurement variables of the PIECES framework were performance, information, economy, control, efficiency, and service. In this study, researchers used quantitative descriptive methods with data sources from questionnaires via google form with 101 respondents, and data processing was carried out using SEM-pls. The results of this study indicated the value of R square was 0.732. It can be concluded that the interpretation of the users’ satisfaction level of the application was 73.2%, which R-square identifies in the Strong/Good category. Several PIECES variables that has a significant effect on people's satisfaction with the JKN mobile application were efficiency and performance variables with P values of 0.004 and 0.033 while variables that did not have significant effect were control, economy, information and services.